DESIGN OF WATER LEVEL CONTROL SYSTEMS USING PID AND ANFIS BASED ON FIREFLY ALGORITHM - Machrus Ali; A N Afandi; Asnun Parwati; Ruslan Hidayat; Cholil Hasyim (Merdeka Malang University, 2019)
At present, a controlling system of the fluid flow measurement is needed in industrial processes. Determination of the water quantity is also used to reduce the volume of water usage in the holding tank varies. The effort to overcome this problem has made using a system for regulating performances while a water flow based on the tank volume controlled using a PID system. This system uses a flow sensor to detect the water speed, an electric ball valve as an actuator. In principles, this tool is used to stabilize the output water speed per minute at a predetermined set point. This study is focused in five designed method comparison in associated with a water level without control, standard PID method, PID-Auto tuning method Matlab, PID-FA method, and ANFIS-PID-FA method. The results of the PID-FA training data are used as an input from ANFIS. From the simulation, it is also found that five control models have different performances while the ANFIS-PID-FA model is performed in the best control model. The ANFIS-PID-FA model has also the smallest overshot and undershot on the water level and output flow of 0.0021 pu, 0.0093 pu, 0.0072 pu, and 0.0096 puDOI : https://doi.org/10.26905/jeemecs.v2i1.2804